2017
DOI: 10.1016/j.brat.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Improving cognitive control in adolescents with post-traumatic stress disorder (PTSD)

Abstract: The adverse impact of posttraumatic stress disorder (PTSD) on the developing mind in adolescence can extend well into adulthood. The developmental malleability of cognitive control capacity in this age group, however, may hold particular promise for cognitive training interventions. The present study investigated the effects of affective working memory (aWMT) compared to placebo-training on cognitive and affective functioning in adolescents with PTSD. 30 treatment-seeking adolescents trained for 20 days on eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 42 publications
4
76
1
1
Order By: Relevance
“…Of the studies reviewed, some achieved positive gains in accuracy for cognitive outcomes (Hoorelbeke & Koster, ; Houben, Dassen, & Jansen, ; Peckham & Johnson, ; Schweizer et al, ; Xiu, Wu, Chang, & Zhou, ; Zhang et al, ), while others did not (Hitchcock & Westwell, ; Hoorelbeke et al, ; Li, Xiao, et al, ). Others demonstrated decreases in response times (Course‐Choi, Saville, & Derakshan, ; Xiu, Zhou, & Jiang, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the studies reviewed, some achieved positive gains in accuracy for cognitive outcomes (Hoorelbeke & Koster, ; Houben, Dassen, & Jansen, ; Peckham & Johnson, ; Schweizer et al, ; Xiu, Wu, Chang, & Zhou, ; Zhang et al, ), while others did not (Hitchcock & Westwell, ; Hoorelbeke et al, ; Li, Xiao, et al, ). Others demonstrated decreases in response times (Course‐Choi, Saville, & Derakshan, ; Xiu, Zhou, & Jiang, ).…”
Section: Resultsmentioning
confidence: 99%
“…Working memory training was associated with improvements in reappraisal (Peckham & Johnson, ), positive emotion regulation (Schweizer et al, ), and positive thoughts when challenged (Hoorelbeke et al, ). There were also decreases in brooding (Hoorelbeke et al, ; Hoorelbeke & Koster, ; Peckham & Johnson, ), post‐traumatic stress disorder symptoms (Schweizer et al, ), depressive symptoms (Hoorelbeke & Koster, ; Zhang et al, ), maladaptive emotion regulation (Hoorelbeke & Koster, ), rumination (Hoorelbeke et al, ), intrusive thoughts (Hotton et al, ), and worry (Course‐Choi et al, ). Following working memory training, those with social anhedonia displayed increased preferences for reward (Li, Li et al, ), which could be viewed as diminishing one problematic aspect of social anhedonia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither study featured robust controls and sample size was limited in one case. However, in a recent well-controlled study, Schweizer et al (2017) found emotional WM training led to significant reductions in post-traumatic stress disorder symptoms (PTSD) in adolescents awaiting treatment for PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Power was established with time as withinsubjects factor, training group as fixed factor and participants as random factors. The effect size for the interaction was estimated as small to medium d = .40, based on our previous training studies in adolescents (35) and adults (21,34). The calculator used was https://jakewestfall.shinyapps.io/pangea/.…”
Section: Participantsmentioning
confidence: 99%